Productive Employment and Decent Work: The Impact of AI Adoption on Psychological Contracts, Job Engagement and Employee Trust - Braganza, Ashley; Chen, Weifeng; Canhoto, Ana; Sap, Serap (Elsevier Science inc, 2021)
This research examines the tension between the aims of the United Nations' Sustainable Development Goal 8 (SDG 8), to promote productive employment and decent work, and the adoption of Artificial Intelligence (AI). Our findings are based on the analysis of 232 survey results, where we tested the effects of AI adoption on workers' psychological contract, engagement and trust. We find that psychological contracts had a significant, positive effect on job engagement and on trust. Yet, with AI adoption, the positive effect of psychological contracts fell significantly. A further re-examination of the extant literature leads us to posit that AI adoption fosters the creation of a third type of psychological contract, which we term "Alienational". Whereas SDG 8 is premised on strengthening relational contracts between an organization and its employees, the adoption of AI has the opposite effect, detracting from the very nature of decent work.
Chen, Weifeng/0000-0002-5850-0759; Canhoto, Ana Isabel/0000-0002-1623-611X; Sarp, Serap/0000-0002-2560-4105;
Keywords: Artificial Intelligence; Psychological Contract; Employee Engagement; Job Trust; Sustainable Development Goals; Decent Work